1987
DOI: 10.1161/01.hyp.9.6_pt_2.iii49
|View full text |Cite
|
Sign up to set email alerts
|

Subpressor infusions of angiotensin II alter glomerular binding, prostaglandin E2, and cyclic AMP production.

Abstract: SUMMARY Angiotensin II (ANG II)Portions of this work were presented at the American Society of Nephrology, December 1982 and 1984, and published in abstract form (Kidney Int 1983;23:277 and 1985;27:256).Address for reprints: Dr. Janice Green Douglas, Department of Medicine, Case Western Reserve University School of Medicine, Cleveland, OH 44106. tration coefficient (K f ) through this action. 6 -7 In certain experimental models of kidney disease, the observed decreases in K { and nephron filtration rate have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…In the above perfusion experiments in which lumens were perfused with an angiotensin II-free solution, the augmented hydrogen ion secretion after intravenous angiotensin II was signaled via the basolateral route ( 12,14). The systemic angiotensin II level under normal conditions in the rat is -1-5 X 10-12 M and rises to -5-10 X 10-12 M after low-dose intravenous angiotensin II administration (22,23). Since membrane receptors facing the tubular lumen also exist (13,14), occupancy of luminal receptors by comparable doses of angiotensin II might also affect transport.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above perfusion experiments in which lumens were perfused with an angiotensin II-free solution, the augmented hydrogen ion secretion after intravenous angiotensin II was signaled via the basolateral route ( 12,14). The systemic angiotensin II level under normal conditions in the rat is -1-5 X 10-12 M and rises to -5-10 X 10-12 M after low-dose intravenous angiotensin II administration (22,23). Since membrane receptors facing the tubular lumen also exist (13,14), occupancy of luminal receptors by comparable doses of angiotensin II might also affect transport.…”
Section: Resultsmentioning
confidence: 99%
“…These studies assessed the relative physiologic importance of basolateral versus luminal effects. The magnitude of transport stimulation by intravenous angiotensin II (which raises systemic angiotensin II level from about 1-5 to 5-10 X 10-12 M [22,23]) with an angiotensin II-free perfusate was compared to that elicited by luminal perfusion with either 1 X 10-12 M (n = 5) or 1 X 10-" M (n = 5) angiotensin II under conditions of a constant basolateral environment.…”
Section: In Vivo Microperfusionmentioning
confidence: 99%
“…The ability for angiotensin II to depress adenylate cyclase activity and intracellular cAMP level has been described in many tissues (1 1, 12), including liver (13)(14)(15), aorta (16), adrenal cortex (17,18), pituitary (19), and testis (20). In the kidney, this signaling process has been shown in cortical homogenates (21), glomeruli (22,23), juxtaglomerular apparatus (24), tubule suspensions (23), and proximal cells in culture (25). In some of these studies, the necessary intermediation of a G1 protein was demonstrated by showing that the decrement in cAMP evoked by angiotensin II was sensitive to pertussis toxin (13,19,20,24).…”
Section: Resultsmentioning
confidence: 99%
“…However, when phorbol ester was perfused in the in vitro rabbit PCT to activate protein kinase C, bicarbonate transport was actually inhibited (10). Another signaling system used by angiotensin II in many cells (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) including those of the PCT (25) involves reduction of adenylate cyclase activity to lower intracellular cAMP concentration. No correlation with renal epithelial cell ion transport has been yet made with this angiotensin II signaling mode.…”
Section: Introductionmentioning
confidence: 99%
“…The downregulation of Ang II receptors in the medulla may be a reflection of events within the glomerulus controlling Ang II production. Because Ang II can upregulate its own receptor within the kidney, 23 we cannot yet be certain whether downregulation in obese SHR was due to excess Ang II or a relative lack of Ang II. Receptors for Ang II have not previously been characterized in an experimental model of nephritis.…”
Section: Discussionmentioning
confidence: 99%